Kansalaiset kaupunkia kehittämässä - Häkli, Jouni; Schulman, Harry; Bäcklund, Pia (Tampere University Press, 2017)
"Urban planning and development are a meeting ground for different experiences and interpretations pertaining to the desireable city, and the ways in which citizens should genuinely be able to participate in the process. This multidisciplinary book explores broadly the question of how to best approach participation today. Instead of aiming at a singular interpretation, the book sets out to develop tools for a better understanding of the different logics behind urban development and citizen participation. The authors explore themes ranging from governmental structures and settings all the way to individual lifeworlds and experiences, and provide several well-founded propositions on what participation is about. The articles give voice to actors from the public sphere, from the third and fourth sectors, as well as to citizens in different social roles and positions. The book serves as a text book in disciplines related to urban development and participation, and as an information source for professionals and citizens interested in the topic."